1997
DOI: 10.1038/sj.bmt.1701023
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline, ciprofloxacin and prednisone failed to prevent transplant-related toxicities in bone marrow transplant recipients and were associated with an increased incidence of infectious complications

Abstract: Summary:Intensive therapy followed by hematopoietic progenitor TNF-␣ (Tumor necrosis factor-alpha) is involved in administration has improved the prognosis of many dismany immunological and inflammatory processes, and eases in the last 30 years. However, this procedure is commight be expected to play an important role in the plicated by secondary events which may endanger the development of BMT-related complications. Triple therpatient's life in 23-35% of cases. 1 Conditioning-related apy (pentoxifylline, cipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 2 publications
0
23
0
Order By: Relevance
“…213 However, none of the consecutive randomized, placebocontrolled trials found pentoxifylline to be effective. [214][215][216][217][218][219][220] …”
Section: Systemically Applied Pharmacotherapeuticsmentioning
confidence: 99%
“…213 However, none of the consecutive randomized, placebocontrolled trials found pentoxifylline to be effective. [214][215][216][217][218][219][220] …”
Section: Systemically Applied Pharmacotherapeuticsmentioning
confidence: 99%
“…[83][84][85] These agents may even be hazardous due to a reported increase of infections. [86][87][88][89] Topical azelastine seems to improve clinical symptoms in patients with aphtous ulceration and Behcets disease; however, the effect in oral mucositis is only accessible from one study. 90 Use of allopurinol mouthwashes for prophylaxis of 5-flurouracil-induced oral mucositis was studied with the hypothesis of inhibiting orotidylate decarboxylase which produces a toxic metabolite of 5-FU.…”
Section: Mouthrinses With Anti-infective and Anesthetic Propertiesmentioning
confidence: 99%
“…The role of systemic inflammation in the development of mucositis was further supported by studies showing that the therapy targeted to alter cytokine expression is able to modify the course of mucositis 32 . Animal 33 and human studies 34 have demonstrated a decrease in the occurrence or severity of mucositis following the administration of TNF inhibitors.…”
Section: Discussionmentioning
confidence: 99%